Evolution of Surgical Management of Hemorrhoidal Disease: An Historical Overview - Pata, Francesco; Gallo, Gaetano; Pellino, Gianluca; Vigorita, Vincenzo; Podda, Mauro; Di Saverio, Salomone; D'Ambrosio, Giancarlo; Sammarco, Giuseppe (Frontiers in Surgery, 2021)
Hemorrhoidal disease (HD) is the symptomatic enlargement and/or distal displacement of the normal hemorrhoidal cushions and is one of the most frequent diseases in colorectal surgery. Several surgical or office-based therapies are currently available, with the aim of being a more tailored approach. This article aimed to elucidate the historical evolution of surgical therapy for HD from ancient times, highlighting the crucial steps, controversies, and pioneers in the field. In contrast with the previous literature on the topic that is often updated to the 1990s, with the introduction of stapled hemorrhoidopexy and transanal hemorrhoidal dearterialization, this article describes all new surgical and office-based treatments introduced in the first 20 years of the 2000s.